Le Rayon vert de Jules Verne. La confrontation ironique des discours météorologiques - Becker, Karin (Studia Romanica Posnaniensia, 2021)
Jules Verne’s Le Rayon vert (1882) is at the same time a scientific novel and a love story, a repertory of knowledge and a criticism of clichés. Telling the amusing attempts of a little group of travelers that tries in vain to catch sight of the “green ray” – the last impression of sunset – on the horizon from the Scottish coast, the author confronts in an ironical way different stereotypical discourses about weather phenomena which coexist in the bourgeois society of the late 19th century. Verne mocks equally scientific, folkloristic and romantic ideas about meteorological observations and uses these opposite explications of the mysteries of nature to characterize his protagonists and to develop the suspense of the narration.